Dominasi Mutu Kinerja Sumber Daya Manusia terhadap Peningkatan dan Pengembangan Kualitas Layanan Perbankan XY - Dwijayanti, Ririn; Anggraini Ardhya Putri, Silviana; Arianto, Bisma (Majalah Ekonomi, 2024)
The quality of Human Resources performance is a benchmark in achieving the vision and mission of the institution. Performance quality is an assessment or quality of an activity that is an achievement of an organization. In banking activitie themselves, performance quality is very important so that there are no errors or fraud from every record made by banking employees. This requires motivation to raise work enthusiasm, training and professional development of bank employees. If employees provide good service to customers, of course it will benefit the bank itself and provide good value. The sample of this qualitative study was 115 employees of Bank XY in Surabaya. Therefore, human resource planning is needed for banking employees, in order to make it easier to plan future workforce demand to anticipate employee shortages in customer service.